Exercise Training in Patients with Pulmonary Hypertension: A Systematic Review and Meta-analysis Körperliches Training bei pulmonaler Hypertonie - ein systematisches Review mit Metaanalyse - Gloeckl, R.; Schneeberger, T.; Boeselt, Tobias; Kenn, K.; Koczulla, A. R.; Held, M.; Oberhoffer, R.; Halle, M. (Pneumologie, 2019)
Background Pulmonary hypertension (PH) is defined as an elevation of mean pulmonary-arterial pressure by >20mmHg at rest, which may lead to right heart failure. Physical exercise has not been regularly recommended for PH patients for fear of symptom deterioration or occurrence of exercise-induced adverse events. Methods Three electronic databases were searched for randomized, controlled trials investigating exercise training in PH patients using the following keywords: pulmonary hypertension OR pulmonary arterial hypertension AND exercise OR pulmonary rehabilitation AND randomized. Results Five studies involving 187 PH patients were included in this systematic review. Exercise programs lasted for 3-12 weeks (e.g. endurance training for 10-45 minutes; 60-80 of the peak heart rate). PH patients significantly improved exercise capacity compared to controls in 6-minute walk distance (+45m; 95 CI: 26m-64m) or peak oxygen consumption (+2.3ml/kg/min; 95 CI: 1.8-2.9ml/kg/min), both p<0.001. Also, physical and mental quality of life improved significantly by exercise training. No exercise-induced adverse events were observed. Conclusion Supervised exercise training can safely and significantly improve physical performance and quality of life in clinically stable PH patients with optimal drug treatment. However, larger studies including a wider range of PH are mandatory.
CRIS-Team Scopus Importer:2023-03-08